Isolation of Chitinolytic Bacteria from Shrimp Waste as a Control of Aedes aegypti Instar III Mosquito Larvae - Pardosi, Lukas (Biodidaktika : Jurnal Biologi dan Pembelajarannya, 2025)
Insect-borne diseases remain a serious health problem in Indonesia, especially Dengue Hemorrhagic Fever (DHF), which can cause mass mortality in developing countries. Biological control, such as using chitinolytic bacteria, is needed to contain the spread of this disease. The methods used include sampling and preparation of shrimp waste, manufacture of chitin agar media, isolation of chitinolytic bacteria, macroscopic and biochemical characterization, maintenance of Aedes aegypti larvae, observation of effects on mosquito larvae, and data analysis. The results obtained there are six isolates that have different morphological characteristics: IS1 to IS6 isolates have a round shape and milky white color, with wavy edges on IS1, IS2, and IS4, and flattened on other isolates. At elevation, IS1 and IS5 are flat, while the other four isolates are convex. Microscopic tests found 2 isolates contained Gram-negative and 4 isolates Gram-positive. The biochemical test of all six isolates was positive. Effect of administration of the concentration that caused the highest time of death of larvae on the fourth day, with a concentration of 15% and an average number of deaths of 4.66. Based on the results of the study, it can be concluded that six isolates of chitinolytic bacteria were successfully isolated, with diverse morphological characteristics, including differences in shape and color. Microscopic tests identified two isolates as Gram-negative and four isolates as Gram-positive. The biochemical test results showed that the six isolates were positive in the catalase, Simmons Citrate Agar (SCA), and Triple Sugar Iron Agar (TSIA) tests. Concentration administration affected the time of larval death, with a concentration of 15% showing the highest mortality rate on the fourth day, with an average death toll of 4.66